Influência da carga orgânica na produção de bio-hidrogênio a partir de resíduo de fecularia em reator ansbbr em batelada alimentada - Tonello, Tamiris Uana (2017)
Energy demand has been met, for the most part, by non-renewable sources of energy, mainly from fossil fuels. These fuels tend to become extinct, so that, in order to guarantee economic, social, and ecological progress,it is necessary to look for renewable alternatives for the generation of energy. Bio-hydrogen production resulting from the biological method stands out due to the possibility of its obtaining from residue. Therefore, this work has the objective of evaluating the efficiency of anaerobic sequential batch reactor with immobilized biomass (AnSBBR) for the production of bio-hydrogen from cassava starch wastewater (CSW). The AnSBBR used in the tests presents mechanical agitation system and total and useful volumes of 6.0 and 4.3 L, respectively. The reactor was kept in a controlled temperature chamber (30 °C). Four experimental conditions (I, II, III, and IV) were carried out in a fed batch with organic volumetric loads (9.0, 13.5, 18.0, and 18.0 g-total sugars L-1d-1) for cycle durations of 4; 4; 3; and 2 h, respectively.Conditions I, II, and IV were inoculated with sludge from an anaerobic reactor from CSW, and condition III was with auto-fermented inoculum. It was found that the inoculum from the anaerobic reactor of the cassava starch effluent influenced the production of biogas in AnSBBR reactors. Condition II showed total sugar conversion of 84%, hydrogen molar productivity of 35.8 mLH2 m-3d-1 and hydrogen yield related to total sugar applied and removed of 2.42 and 4.6 molH2 Kg total sugars-1, respectively. In condition III (18 g-total sugars L-1d-1 and TDH of 3 h) with auto-fermented inoculum, there was no hydrogen production; however, it presented 98.47% of total sugar conversion throughout the operation. As for the intermediate products, there was an increase of acetic, butyric, and propionic acids in the reactor. However, the lactic acid did not increase, probably due to consumption by microorganisms, except in condition IV.